Lourenço Mutarelli, a imagem e a palavra: concepções pós-autônomas sobre quadrinhos e literatura - Souza, Arthur Dias de (2018)
Considering the absence of universalizing concepts capable of evaluating the transformations in the artistic field in the contemporary period, this research proposes ways of developing critical work through a theoretical and methodological framework that privileges the description of artistic productions to approximate the aesthetic fact (CANCLINI, 2016a). The general objective of this research is to decant from the problematizations of the comic book of Lourenço Mutarelli, entitled A caixa de areia: ou eu era dois em meu quintal (2006), a conception of artistic making that allows the development of an instrument of analysis for the novel by the same author, O natimorto: um musical silencioso (2009). Thus, it is intended to elaborate a methodology to present the process of constitution of Mutarelli's productions from his own artistic work, understanding how the process of problematic formalization of this artist is structured, a concept proposed by Flora Süssekind (2013) for the analysis of articulation of verbal and nonverbal elements in the composition of the literary text. From what critics identify as a supposed plastic record (SÜSSEKIND, 2013) present in the novel O natimorto, I establish research paths to think about the problematizations of limits and boundaries that destabilize the autonomy of the artistic field and the separation of the different arts. To do so, I base myself on Jacques Rancière's (2005) conception of distribution of the sensible, in order to investigate the relations between word and image within what the philosopher understands as the regimes of identification of the arts. In the contemporary period, the aesthetic regime of the arts is in operation, responsible for a disarray of the relations between word and image, between literature and other arts. In this sense, Florencia Garramuño's notion of a literature understood as an expanded literary and critical field, in which different formats and medias are intertwined, helps this research on how the literary can be configured in the contemporary Brazilian scenario.